Pengaruh’fungsi Operasional Kepegawaian dan Lingkungan Kerja Non Fisik terhadap Kinerja Karyawan PT. PLN (PERSERO) Pusat Manajemen Proyek Semarang - Putri, Febita Vira Nugraha; Samasta, Almira Santi (Universitas Batanghari, 2024)
The purpose of this research is to determine the influence of Staff Operational Functions and Non-Physical Work Environment on Employee Performance at PT. PLN (Persero) Semarang Project Management Center. This research uses quantitative descriptive methods. The sample in this research is all employees who are members of PT. PLN (Persero) Semarang Regional Project Management Center with 100 employees. The analytical method for this research uses multiple linear analysis techniques using SPSS version 26 software. The research results show that : (1) Human Resource Planning (2) Performance Appraisal (3) Payroll System (4) Non-Physical Work Environment has a positive and significant effect on Employee performance. However, training shows a negative and significant influence on employee performance.